Romano Illo - Cioaba, Luminita Mihai (Romania, 2006)
The film is telling a fictious mythological story of the Roma who were once the favoured peoples of God. The images are showing Roma as if in fairy tales: in wild nature blessed with abundance, in beautiful oriental dresses, surrounded by happiness: laughing and dancing. Folklore dominates the film, yet there are certain attempts to present the lives of the Roma living in Romanian villages in 2006.
"Project accomplished with the support of Open Society Institute Budapest. Grant number 40010040.
Duration: 00:38:00
Keywords: Fiction films